2019
DOI: 10.1002/ejic.201900975
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Active Guanidines with One or Two Guanidino Groups and Their Integration in Low‐Dimensional Perovskite Structures

Abstract: Redox‐active guanidines are versatile reagents in redox and proton‐coupled electron‐transfer (PCET) reactions. Recently, they were integrated as sacrificial electron donors for the prohibition of metal oxidation in perovskite materials. Herein we report the synthesis and characterization of several new redox‐active guanidines with aromatic (benzene, naphthalene or anthraquinone) cores. Two of these compounds are then integrated in lead iodide materials. The structure, thermal stability and optical band‐gap of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 122 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…N-Ethylcarbazole exhibits an E ox value of 1.12 Vv s. SCE, [30] translating into a value of 0.66 Vv s. Fc + /Fc. [31] Since previous experiments showed that substrates with ar edoxp otential of up to 0.77 V vs. Fc + /Fc could be oxidized, [28] it was clear that the potential is not too high for ar eactionw ith initial electron transfer.I n our experiments, one equivalent of 1(BF 4 ) 2 or 1(ClO 4 ) 2 (see the Supporting Information for synthesis and characterization of this new salt) was reactedw ith N-ethylcarbazole in the presence of 16 equivalents of HBF 4 •OEt 2 .A cetonitrile wasc hosen as solvent, since the protonated, oxidized guanidine (1 + 2H) 4 + that forms immediatelyi nt he presenceo fastrong acid, is not soluble in nonpolarsolvents such as CH 2 Cl 2 .Indeed, near quantitative conversion (94 %a nd 95 %, respectively)w as obtained within 1h reaction time. Recently,V enkatakrishnan et al showedt hat reaction of DDQ or CA with N-ethylcarbazole gives quantitative yield (> 99 %) of the bicarbazole coupling product in very short time when carriedo ut in CH 2 Cl 2 solution with an excess of methanesulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…N-Ethylcarbazole exhibits an E ox value of 1.12 Vv s. SCE, [30] translating into a value of 0.66 Vv s. Fc + /Fc. [31] Since previous experiments showed that substrates with ar edoxp otential of up to 0.77 V vs. Fc + /Fc could be oxidized, [28] it was clear that the potential is not too high for ar eactionw ith initial electron transfer.I n our experiments, one equivalent of 1(BF 4 ) 2 or 1(ClO 4 ) 2 (see the Supporting Information for synthesis and characterization of this new salt) was reactedw ith N-ethylcarbazole in the presence of 16 equivalents of HBF 4 •OEt 2 .A cetonitrile wasc hosen as solvent, since the protonated, oxidized guanidine (1 + 2H) 4 + that forms immediatelyi nt he presenceo fastrong acid, is not soluble in nonpolarsolvents such as CH 2 Cl 2 .Indeed, near quantitative conversion (94 %a nd 95 %, respectively)w as obtained within 1h reaction time. Recently,V enkatakrishnan et al showedt hat reaction of DDQ or CA with N-ethylcarbazole gives quantitative yield (> 99 %) of the bicarbazole coupling product in very short time when carriedo ut in CH 2 Cl 2 solution with an excess of methanesulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Previous quantum-chemical calculations indicate that (1 + 2H) 4 + is an even stronger oxidant in PCET reactions than DDQ or CA. [28] The reactionr equires the use of 1.5 equivalents of 1 2 + .T his can be explained by the considerably lower redox potential of the triphenylene product (0.72 Vv s. Fc + /Fc in CH 2 Cl 2 )c ompared with the reactant (1.22 Vv s. Fc + /Fc in CH 2 Cl 2 for 3,3''-dimethoxy-3',4'-dimethyl-o-terphenyl), leadingt op referred oxidation of the product by (1 + 2H) 4 + to the radicalm onocation. The formation of this radical cation leads to broad signals in the NMR spectra,a nd therefore the reaction was quenched before analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypsochromic shifts upon protonation have been reported previously for guanidines. [27] Recently,s uch shifts and the influence of intermolecular hydrogen bonding to anionswere analysed. [28] In clear difference to all other GFAc ompounds, blue fluorescence is switched on by protonation.…”
Section: Protonation-inducedf Luorescencementioning
confidence: 99%